2012
DOI: 10.5455/2320-1770.ijrcog000712
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of complications of abdominal and vaginal hysterectomy

Abstract: INTRODUCTIONHysterectomy is one of the most common surgical procedures performed by the gynaecologist. It can be performed by abdominal and vaginal route. Vaginal hysterectomy (VH) has several advantages over abdominal hysterectomy (TAH), and may be appropriate for up to 80% of benign uterine conditions. 1,2 Evidence supports TAH only when documented pathologic conditions preclude the vaginal route. 3,4 Even recent study in United States shows 82% were TAH, only 13% were VH and 5% were laparoscopic assisted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 27 publications
7
13
0
Order By: Relevance
“…This is similar to the study by Shanthini et al who reported 5.7% incidence of wound infection in the TAH group. 15 Kovac et al reported similar outcome in their comparative study between abdominal and vaginal routes. 16 Bharatnur et al in their study showed that overall post-operative complications are more in abdominal hysterectomy group which is similar to our results.…”
Section: Resultssupporting
confidence: 60%
“…This is similar to the study by Shanthini et al who reported 5.7% incidence of wound infection in the TAH group. 15 Kovac et al reported similar outcome in their comparative study between abdominal and vaginal routes. 16 Bharatnur et al in their study showed that overall post-operative complications are more in abdominal hysterectomy group which is similar to our results.…”
Section: Resultssupporting
confidence: 60%
“…These results were comparable to the study by Mahasani V et al 9 In the study by Fatima et al bladder injury occur in 4 cases (2.3%) of TAH and 1 case (1.9%) of VH, while ureteric injury occurred only in 1 case (0.6%) of TAH but no case in VH. 10 In the TLH group of our study hemorrhage occurred in 4 patients (13.3%), 1 patient (3.3%) had bladder injury and 1 patient (3.3%) had hemorrhage with ureteric injury ,which was comparable to study by Patel R et al (bladder injury occurred 2 cases of TLH). 7 In Sutasanasuang intra-operative complication rate in TAH was 16.67% which was found comparable to our study (20%).…”
Section: Discussionsupporting
confidence: 78%
“…In the studies by V. Mahasani et al (TAH 1 hour 20 minutes and NDVH 45 minutes) and Fatima et al (TAH= 99.2 minutes and VH= 79.6 minutes) operating time was less for the vaginal route compared to the abdominal. 9,10 Mean operating time in the TLH group was 142.3±33.7 minutes. In the study by Patel et al in laparoscopic hysterectomy took almost double the time as NDVH (LH 2 to 4 hours; NDVH 1 to 2 hour).…”
Section: Discussionmentioning
confidence: 99%
“…Kumari S et al noted bladder injury in 0.78% patients whereas Shanthini et al noted bladder injury in one (1.9 %) patient. 13,20 We noted bladder injury in three (2.8%) patients and bowel Postoperative complications were minimal which included febrile morbidity and UTI in 7.4% and 6.5% respectively which were tackled successfully. Six patients (5.6%) received blood transfusion either in intraoperative or post-operative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Blood loss ranged from 30 ml-160 ml in different studies. 13,20 Visceral injuries like bladder and bowel injuries were reported differently in different studies. Kumari S et al noted bladder injury in 0.78% patients whereas Shanthini et al noted bladder injury in one (1.9 %) patient.…”
Section: Discussionmentioning
confidence: 99%